Violence, Victimhood and Trauma: Exploring the Partition Narratives of Bombay Cinema. Issue 1 (1st January 2017) - Mubarki, Meraj Ahmed
Abstract : This article focuses on a corpus of Hindi films that, from a variety of ideological and generic viewpoints, articulate Hindi cinema's presentation of India's Partition trauma. It asserts that the cinematic mediation of this trauma appears symptomatic of the vicissitudes of larger discourses at work, and can be categorized into three phases with definite trajectories; wherein Partition first appears as a "denial, " where the traumatic episode becomes a Barthesian absence in the immediate aftermath of the Partition. Later, Partition reappears as "supracommunal trauma" transcending established national boundaries or spheres of sectarian interest in deference to the national conciliation project of Nehruvian secularism. In its third trajectory of the Hindutva milieu, films like Gadar and Hey Ram mark the "expropriation" of the Partition narratives from collective consciousness of experiences into a purely sectarian phenomenon.